Effects of Environmental Educations for Organisations - Strand, Lisa; Mleczkovicz, Rickey (My University, 2017)
This study investigate what influence an basic environmental education has on an organisation as well as what conditions promotes change. The evaluation focuses on the basic environmental education by Ekocentrum. The main collection of data was done with a survey that was sent to previous participants of Ekocentrum’s education. The survey was completed with seven interviews. The analysis was performed in SPSS and the method which gave best result was comparing mean values. The most important effect of the education found was the change of mindset and the awareness of the environment at the work places. Furthermore, built-on approach of changes were common, instead of more profound changes. Of the different causes investigated, none correlate substantial with the effects of the environmental education. The biggest influence comes from the participants position in the organisation and their level of anticipation towards the education. Besides the investigated factors the setup of the education and the environmental awareness of the management was mentioned in the survey as big influences on the changes made. As this is to be considered as a pilot study there are many possible ways to go through with future studies.
Keywords: Building Futures; Hållbar utveckling; Pedagogik; Pedagogiskt arbete; Sociologi (exklusive socialt arbete, socialpsykologi och socialantropologi); Building Futures; Sustainable Development; Pedagogy; Pedagogical Work; Sociology (excluding Social Work, Social Psychology and Social Anthropology)